Konservasi Tanah Terhadap Lahan Terdegradasi Melalui Pengorganisasian Masyarakat Dukuh Gumuk Desa Meriyan Kabupaten Boyolali - muhammad wildan ainun naim (Empower : Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to determine land conservation techniques and their impact on degraded land in Dukuh Gumuk, Mriyan Village, Boyolali Regency. The benefits to be achieved with this research are a first step to make people aware of the importance of maintaining soil sustainability in order to avoid the threat of land degradation. The research method used is descriptive qualitative with data collection techniques through interviews, observation and documentation. The results showed that the degraded land conservation technique in Dukuh Gumuk used vegetative methods, namely by using perennials such as avocado, kepel, persimmon, mango, and coffee. The conservation was carried out by the community and the government of Dukuh Gumuk, accompanied by the Rural Technology Development Institute (LPTP). Vegetation conservation methods can maintain soil stability caused by the eruption of Mount Merapi, land management that is left open and low awareness of the community in maintaining soil sustainability. The conservation activities also help create new sources of income for the community through coffee powder processing production centers.